University Entrepreneurship Educaiton and Entrepreneurial Intentions during Post-Pandemic Era: The Mediating Effects of Psychological Capital - Chun-Chieh Liao; Lin-Ju Cheng (National Taipei University of Education, 2021)
This study employs entrepreneurship and crisis management theory as the research framework, focusing on the formation of college students' entrepreneurial intentions before and after the coronavirus disease pandemic (COVID-19) in 2020. The independent variable considered in this study is entrepreneurship education which is not limited to formal classroom instruction but through informal mechanisms such as competition, or mentorship. The study proposes that besides direct impact on entrepreneurial outcomes, entrepreneurship education is also facilitated by the mediation effect of psychological capital. This research particularly focuses on two aspects: optimism and entrepreneurial self-efficacy, which had been found important for both entrepreneurship education and the development of entrepreneurial intentions in previous literature. The study was conducted using two sub-samples of Taiwanese university graduates (before and after the COVID-19 shocks) and used structural equation modeling, bootstrapping method, and invariance test of multiple group structural equation modeling to test six hypotheses. Regarding the direct effects, the results indicate that both entrepreneurship education and entrepreneurial self-efficacy have positive direct effects on entrepreneurial intentions, whereas the effect of optimism does not. COVID-19 shocks strengthened the above effects. As for the mediation analyses, the results support that entrepreneurship education has an impact on entrepreneurial intentions through both optimism and entrepreneurial self-efficacy. The COVID-19 pandemic also deepens the relationship between entrepreneurship education and entrepreneurial intentions through psychological capital (optimism and entrepreneurial self-efficacy). The study concludes that through the COVID-19 shocks, entrepreneurship education not only plays a more important role in directly boosting entrepreneurial intentions but also strengthens the mediation effects through developing psychological capital. The study suggests that the government, corporations, and universities could offer a more abundant environment for entrepreneurship education in universities. Universities could provide some courses and activities related to entrepreneurship to cultivate students' hard and soft skills, and entrepreneurial self-efficacy and optimism, mitigating negative impacts on entrepreneurial intentions to beat the coronavirus pandemic.